Controlled Study of 50 Hz Repetitive Transcranial Magnetic Stimulation for the Treatment of Parkinson’s Disease - Benninger, David H. (2012)
OBJECTIVE: To investigate the safety and efficacy of 50Hz repetitive Transcranial Magnetic Stimulation(rTMS) in the treatment of motor symptoms in Parkinson’s disease(PD). BACKGROUND: Progression of PD is characterized by the emergence of motor deficits, which eventually respond less to dopaminergic therapy and pose a therapeutic challenge. RTMS has shown promising results in improving gait, a major cause of disability, and may provide a therapeutic alternative. Controlled studies suggest increasing stimulation frequency might enhance therapeutic efficacy. METHODS: In this randomized, double blind, sham-controlled study, we investigated safety and efficacy of 50Hz-rTMS of the motor cortices in 8sessions over 2weeks. Assessment of safety and clinical efficacy over a 1-month period included timed tests of gait and bradykinesia, UPDRS and additional clinical, neurophysiological and neuropsychological parameters. In addition, safety of 50Hz-rTMS was tested with EMG-EEG-monitoring during and after stimulation. RESULTS: We investigated 26 patients with mild to moderate PD: 13 received 50Hz-rTMS and 13 sham-stimulation. 50Hz-rTMS did not improve gait, bradykinesia, global and motor UPDRS, but there appeared a short-lived “on”-state improvement in activities of daily living (UPDRS II). 50Hz-rTMS lengthened the cortical silent period, but other neurophysiology and neuropsychological measures remained unchanged. EMG/EEG recorded no pathological increase of cortical excitability or epileptic activity. There were no adverse effects. CONCLUSION: 50Hz-rTMS of the motor cortices appears safe, but fails to improve motor performance and functional status in PD. Prolonged stimulation or other techniques with rTMS might be more efficacious, but need to be established in future research.